Unit commitment risk assessment of interruptible loads in the operating reserve of Luzon grid - Mendoza, Oliver G. (2009)
Load interruptions form part of a scheme in a power system which enables the grid to recover from a deteriorating frequency resulting from an outage of a generating facility or transmission line/ equipment. Load interruptions can also be used as a part of the total operational reserve of a system.A probabilistic approach in establishing a unit commitment risk model for Luzon Grid, wherein units are committed based on the system firm load and a specified operating risk criterion, was used to study the security of the Grid. Several scenarios are simulated to determine the level of interruptible load and allowable time delay of interruption needed to restore the operating risk to an allowable level in a given firm load. The operating reserve is then evaluated by comparing the level of risk of utilizing only the spinning reserve as opposed to combined spinning and interruptible load.
"October 2009."
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman.
Keywords: Electric power systems -- Luzon (Philippines).; Mathematical optimization; Electric power-plants -- Load -- Management; Electric power system -- Risk assessment -- Luzon (Philippines)